Center of Excellence for Water: The Project - Elshayeb, Yasser (2019)
As part of the seminar held by the International Food Policy Research Institute (IFPRI) in collaboration with IWMI, World fish and ICARDA “Options for improving irrigation water efficiency for sustainable agricultural development”.